Diagnosis of the change in spatial configuration of fruticulture in the State of Espírito Santo, Brazil, in the years 2011 and 2016 - Galeano, Edileuza Vital; Ventura, José Aires; Souza, Renzo Caliman; Silva, Bruce Francisco Pontes da (Geografares, 2019)
In the state of Espírito Santo, Brazil, recently the fruit crops was negatively affected by the climatic adversities and one new productive rearrangement has been verified. In this context, we tried to explore the average productivity of the fruit crops between the years 2011 and 2016, identifying patterns of spatial location. The hypothesis of spatial dependence was corroborated and in 2011 a high productivity cluster (HH) was identified, which comprises seven municipalities in the extreme North of the state. The study showed that there was a significant change in the configuration and location of the clusters in 2016. Despite the advances obtained in the sector, the study evidenced that the fruticulture in Espírito Santo showed to be poorly prepared for situations of climatic adversity. These results can aid in making technical decisions and future policies for the sector.